Trade Liberalization and the Canadian Pulp and Paper Industry - Haviland, William; Cape, Edward; Takacsy, N.S (Heritage, 2019)
The economic impact of free trade among the North Atlantic countries on the Canadian pulp and paper industry is here discussed in a detailed analysis of costs and marketing